The Effect of Social Media Marketing and Online Advertising on Purchase Decisions through Brand Trust - Sri Murtiasih (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to examine the impact of digital marketing strategies, particularly social media marketing and online advertising, on consumer purchase decisions in coffee shops, with brand trust serving as a mediating variable. The research seeks to understand how digital marketing efforts shape consumer perceptions and behaviors in an increasingly competitive coffee shop industry. Using a quantitative research design, primary data were collected from 150 respondents through a purposive sampling technique, targeting consumers in the Jabodetabek area (Jakarta, Bogor, Depok, Tangerang, and Bekasi). Data were obtained via an online questionnaire distributed through Google Forms and analyzed using SmartPLS software. The analysis included both outer model testing and inner model testing. The findings reveal that social media marketing and online advertising significantly influence brand trust, which in turn has a positive and significant effect on purchase decisions. However, social media marketing does not directly affect purchase decisions but exerts an indirect influence through brand trust. These results highlight the pivotal role of brand trust as a mediator and suggest that coffee shop businesses should prioritize trust-building digital marketing strategies to strengthen consumer loyalty and drive purchase decisions.